2017
DOI: 10.1620/tjem.241.21
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genotype 2 HCV in Serotype-1 Hepatitis C Patients Unresponsive to Daclatasvir plus Asunaprevir Treatment

Abstract: It is important to determine the genotypes or serotypes of hepatitis C virus (HCV) in patients before treatment with direct-acting antiviral agents (DAAs), because the effects of DAAs differ among genotypes. In Japan, two tests for HCV typing are available clinically, but only serotyping, not genotyping, is approved by the public health insurance. Although most serotype-1 Japanese patients are infected with genotype 1b HCV, it is known that a small proportion of patients show different results from two typing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…In Japan, an HCV serotyping assay using non-structural protein 4 (NS 4)-specific antibodies is commonly used (3), as an HCV genotyping assay based on the nested PCR method is not approved for coverage by the national health insurance program. When determining HCV genotypes, the frequency of discrepancy between the serotype and genotype is reported to be low (4,16,17), but some clinically problematic cases have been reported (5)(6)(7). Such discrepancies may be caused by coinfection of different genotypes of HCV (6) or infection with an intergenotypic recombinant virus (7).…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, an HCV serotyping assay using non-structural protein 4 (NS 4)-specific antibodies is commonly used (3), as an HCV genotyping assay based on the nested PCR method is not approved for coverage by the national health insurance program. When determining HCV genotypes, the frequency of discrepancy between the serotype and genotype is reported to be low (4,16,17), but some clinically problematic cases have been reported (5)(6)(7). Such discrepancies may be caused by coinfection of different genotypes of HCV (6) or infection with an intergenotypic recombinant virus (7).…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al reported that at least 1.8% (3/168) patients who were treated with daclatasvir and asunaprevir, showed discrepancies in their HCV serotype and genotype examination results. Importantly, all of the three patients failed to respond to daclatasvir and asunaprevir (24). Thus, it is possible that a certain number of patients, for whom only an HCV serotype examination has been conducted (because this is the only examination approved in Japan) and who have failed to respond to daclatasvir and asunaprevir treatment, might have HCV genotype 2 infection.…”
Section: Discussionmentioning
confidence: 99%